Object Dimension Inspection Utilizing 3D Laser Scanner - Al-Faiz, Mohammed Z.; Salih, Omar M. (Nahrain University College of Engineering Journal, 2018)
In this paper, the processes of 3D LASER scanning and dimension inspection were simulated for certain dimensions object. The scanning operation is divided into two major modes, Searching Mode and Scanning Mode. In scanning mode two sub-processes (scanned point validation and plane fitting) are introduced, i.e. to find the plane which contains most of scanned points. The final step is the decision making, which gives a decision about acceptance or rejection of thescanned manufactured object. The proposed algorithm is successfully applied to seven cases. One of them which has the exact dimensions andthis case has been accepted. The other six cases, which have different dimensions, have been rejected.